The construction of pad foundation / 'Ainaa 'Arifah Awang Omar - Awang Omar, 'Ainaa 'Arifah (Universiti Teknologi MARA, Perak, 2018)
Foundation is the element structure which connects it to the ground and transfers loads from the structure to the ground. There are two types of foundation which is shallow and deep foundation. Therefore, this report will discuss about the pad foundation more detail based on the project at Fattah home Design & Construction, Kepala Batas, Pulau Pinang. The objective of this report is to identify the installation method of pad foundation and problem encountered and solution method during the construction. An observation is done through on site visit at the construction site and interview by asking an experienced person in construction industry. As an addition, books and websites also had been used as the medium that support the information and data collected. To conclude, foundation is an important structure in the construction industry as it will sustain and transmit loads from upper structure and spread it to the earth.